Comparison of targeted percutaneous vertebroplasty and traditional percutaneous vertebroplasty for the treatment of osteoporotic vertebral compression fractures in the elderly - Lingli Yuan; Jianzhong Bai; Chunhui Geng; Guansheng Han; Wendi Xu; Zhongchuan Zhang; Hong Luo; Xunbing Zhu (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Objective To investigate the clinical effect of precise puncture and low-dose bone cement in percutaneous vertebroplasty (PVP). Methods Sixty patients with osteoporotic vertebral compression fracture (OVCFs) who were treated with PVP in our hospital from July 2018 to June 2019. These included patients were divided into group A (N = 30) and group B (N = 30). Group A has punctured to the fracture area accurately and injected with a small dose of bone cement, the group B was injected with a conventional dose of bone cement. The operation time, the amount of bone cement injection, the number of X-rays, the VAS scores, the leakage rate of bone cement, and the incidence of adjacent vertebral fractures were compared between the two groups. Result The operation time, fluoroscopic times, and bone cement volume in group A are less than that in group B (P < 0.05). Patients in group A had a lower incidence of cement leakage and adjacent vertebral fracture than that in patients in group B. There was no significant difference in postoperative pain relief between the two groups. Conclusions Precise puncture and injection of small doses of bone cement can reduce the number of X-ray fluoroscopy, operation time, amount of bone cement injection, reduce the rate of bone cement leakage and the incidence of adjacent vertebral fractures, which is a safe and effective surgical approach for the treatment for the aged with OVCFs.